Molecular and serological detection of Theileria equi and Babesia caballi in donkeys (Equus asinus) in Brazil - Machado, R. Z. [UNESP]; Toledo, C. Z. P. [UNESP]; Teixeira, M. C. A. [UNESP]; Andre, M. R. [UNESP]; Freschi, C. R. [UNESP]; Sampaio, P. H. [UNESP] (Elsevier B.V., 2012)
Piroplasmosis in donkeys has been recognized as a serious problem of major economic importance, since the affected animals manifest loss of appetite and decreased working capacity. The present work is aimed at detecting infection or exposure of donkeys in São Paulo, Brazil to Theileria (T.) equi and Babesia (B.) caballi using molecular and serological approaches. EDTA-blood and serum samples were collected from 88 donkeys (Equus asinus). From 88 sampled donkeys, 65 (73.86%; 95% confidence interval, PI = 63.41, 82.65) and 82(93.2%; 95% confidence interval, PI = 85.75, 97.46) animals showed IgG antibodies to T. equi (by ELISA) and B. caballi (by IFAT), respectively. Twenty-eight (31.81%; 95% confidence interval, PI = 22.3, 42.61) and 18(20.45%: 95% confidence interval, PI = 12.6, 30.39) donkeys were positive to T. equi and B. caballi nested PCR assays, respectively. The results indicated that T. equi and B. caballi are prevalent among donkeys in Brazil. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Theileria equi; Babesia caballi; Donkeys; Brazil